Analysis of the Attack Area on the Indonesian Junior Team Volleyball Game at the 2019 Asean School Games - Wahyudi, Agung; Wijayanti, Dwi Gansarsanti (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2022)
and the Indonesian women's team won in 2013 and 2014. This achievement became a discussion regarding the strategy used by the coach in determining a good area of attack so that the attacks created would not be in vain. and earn points. Therefore, it is necessary to have an analysis to determine the variation of the effective attack area. This will later become a guideline for coaches to improve the athlete's attacking ability. This descriptive research using the observational method was conducted at the Multipurpose Sports Hall of UIN Walisongo Semarang on 19-23 July 2019 with a research population of Indonesian men's and women's volleyball players at the 2019 Asean School Games. Using non-probability sampling techniques, a sample of 24 athletes was obtained. which is observed using an observation sheet that contains indicators of the success of the attack. After analyzing the data using percentages, it is known that on average 89.58% of the Indonesian Men's Team tends to attack at positions 1, 6, and 5. This is similar to the Indonesian Women's Team, which 85.99% of their attacks also lead to position 1, 6, and 5